Comparative analysis and characterization of soluble factors and exosomes from cultured adipose tissue and bone marrow mesenchymal stem cells in canine species - Villatoro, Antonio J; Alcoholado Cueto, Cristina; Martín Astorga, María del Carmen; Fernández, V.; Cifuentes-Rueda, Manuel; Becerra-Ratia, José (Elsevier, 2019)
The two main sources of mesenchymal stem cell (MSCs) in the canine species are bone marrow (cBM-MSCs) and adipose tissue (cAd-MSCs). The secretion of multitude bioactive molecules, included under the concept of secretome and found in the cultured medium, play a predominant role in the mechanism of action of these cells on tissue regeneration. Although certain features of its characterization are well documented, their secretory profiles remain unknown. We described and compared, for the first time, the secretory profile and exosomes characterization in standard monolayer culture of MSCs from both sources of the same donor as well as its immunomodulatory potential. We found that despite the similarity in surface immunophenotyping and trilineage differentiation, there are several differences in terms of proliferation rate and secretory profile. cAd-MSCs have advantages in proliferative capacity, whereas cBM-MSCs showed a significantly higher secretory production of some soluble factors (IL-10, IL-2, IL-6, IL-8, IL-12p40, IFN-γ, VEGF-A, NGF-β, TGF-β, NO and PGE2) and exosomes under the same standard culture conditions. Proteomics analysis confirm that cBM-MSCs exosomes have a greater number of characterized proteins involved in metabolic processes and in the regulation of biological processes compared to cAd-MSCs. On the other hand, secretome from both sources demonstrate similar immunomodulatory capacity when tested in mitogen stimulated lymphocyte reaction, but not in their exosomes at the dose used. Considering that the use of secretome open as a new therapeutic strategy for different diseases, without the need to implant cells, those biological differences should be considered, when choosing the MSCs source, for either cellular implantation or direct use of secretome for a specific clinical application.
Keywords: Células madre; Cell therapy; Exosomes; Mesenchymal stem cells; Regenerative medicine; Secretome